Assessing the Feasibility of Harnessing Hydropower from Libya’s Artificial River Drinking Pipes: A Renewable Energy Opportunity - Abraheem.A.M; KHALID. AL M. S; A.F. IKRAIAM (African Journal of Advanced Pure and Applied Sciences, 2024)
Water is an essential element in human daily life and a limited natural resource. Small hydropower represents an efficient and reliable form of clean, renewable energy. It is environmentally friendly and easy to operate, with low operating costs. The question of whether Libya’s working artificial river could modernize its extensive network of drinking water pipes with hydroelectric turbines is an interesting one. However, this question has not been widely answered. However, the research presented in this article aims to address this issue by exploring the untapped potential of artificial river drinking pipes in Libya as an energy source. In Libya alone, there are 3,700 kilometres of drinking water pipelines running under the artificial Libyan River. We have previously published this study by designing and analysing the Libya Artificial Rivers Hydropower Model (LMR HEM) at the Renewable Energy Laboratory at Bright Star University. In addition, microtubule turbines (MPT) have been developed and used in tap water pipelines. The MPT is powered by the kinetic energy of water, which drives the generator to produce usable electrical energy through the conduction shaft. This energy is then used to charge the water supply pipeline (WSP) detector battery after transmitting an AC electrical signal. Ultimately, this system achieves the conversion of fluid kinetic energy into mechanical energy.